An Electronic Health Record Investigation of Lenticulostriate Vasculopathy Features - Frankovich, Jennifer; Egan, Maximillian; Mahony, Talia; Benitz, William; Shaw, Gary (American Journal of Perinatology, 2017)
Objective Lenticulostriate vasculopathy (LSV) is characterized by linear hyperechogenicities in the basal ganglia found on the head ultrasounds of infants. We reviewed electronic health records of infants with and without LSV to investigate whether physician dictations indicated symptoms which could reflect subtle basal ganglia injury.Study Design In a case–control study, we analyzed data from 46 infants with LSV and 127 controls. Infants were stratified between term and preterm birth. Odds ratios (ORs) and 95% confidence intervals were calculated for tone abnormalities, apnea, feeding difficulties, seizures, and movement abnormalities in the presence of LSV.Results Both term and preterm infants with LSV showed elevated risks for tone abnormalities (OR: 3.6 and 2.9, respectively). Term infants with LSV showed elevated risks for hypotonia (OR: 4.3), apnea (OR: 2.9), and feeding difficulties (OR: 4.1). Preterm infants with LSV showed elevated risks for truncal hypotonia (OR: 3.9) and hyperreflexia (OR: 3.9).Conclusion Our findings provide some evidence that LSV is associated with an increased risk of early signs of abnormal development, possibly relating to signs of subtle basal ganglia injury. Historically LSV has been considered incidental. The associations identified here suggest that LSV findings are worthy of further study.
Keywords: hyperechogenicity; head ultrasound; electronic medical records; tone abnormalities